1999
DOI: 10.1016/s0014-5793(98)01658-5
|View full text |Cite
|
Sign up to set email alerts
|

The structure of human parathyroid hormone‐related protein(1–34) in near‐physiological solution

Abstract: Parathyroid hormone-related protein plays a major role in the pathogenesis of humoral hypercalcemia of malignancy. Under normal physiological conditions, parathyroid hormone-related protein is produced in a wide variety of tissues and acts in an autocrine or paracrine fashion. Parathyroid hormone-related protein and parathyroid hormone bind to and activate the same G-protein-coupled receptor. Here we present the structure of the biologically active NH P -terminal domain of human parathyroid hormone-related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The peptides bind to the ECD as amphipathic ␣-helices that contact the hydrophobic groove in the ECD, consistent with NMR solution structures of the isolated peptides that showed ␣-helical structure in the 15-34 fragments of the ligands (42,43). Two of the three invariant residues in the 15-34 fragments, Arg-20Ј and Leu-24Ј, anchor the interaction with the ECD.…”
Section: Discussionsupporting
confidence: 76%
“…The peptides bind to the ECD as amphipathic ␣-helices that contact the hydrophobic groove in the ECD, consistent with NMR solution structures of the isolated peptides that showed ␣-helical structure in the 15-34 fragments of the ligands (42,43). Two of the three invariant residues in the 15-34 fragments, Arg-20Ј and Leu-24Ј, anchor the interaction with the ECD.…”
Section: Discussionsupporting
confidence: 76%
“…These structures have been combined with a computer-generated model of the membrane-embedded regions to provide a structural model of the PTH1 receptor [57,58] (see below). most studies find α-helical structure [67][68][69][70][71], specifically an α-helix in the C-terminal region and a smaller α-helical domain in the N-terminal region (Table (1)). The location and size of the helices is generally similar in PTH(1-34) and PTHrP(1-34) ( Table (1), compare line 1 and 5), indicating a similar secondary structure despite the very different primary structures in the C-terminal region.…”
Section: Structural Properties Of Pth Receptorsmentioning
confidence: 99%
“…On the other hand, Wray et al3 and Pellegrini et al14 reported that there was no sound experimental evidence for any significant tertiary structure. The group of Marx et al15–17 reported the presence of very weak interhelical, intramolecular interactions, indicative of a tertiary structure for 1–37, 1–34, 3–37, and 4–34 PTH fragments in TFE‐free solutions. These authors concluded that, due to flexibility of the loop region around Gly12, the relative spatial orientation of the two N‐terminal and C‐terminal helical segments is not fixed, so that no particular tertiary structure is preferred.…”
Section: Introductionmentioning
confidence: 99%